Celebrating Howard Watkins' 40th Birthday in Backyard - Watkins, Howard::::::::: (1987)
Backside of Joe Floyd Asher, Gene Zack, and Evo Bluestein playing violin with Jemmy Bluestein playing banjo Robin Watkins in yellow dress watching